Evaluation of pharmacokinetics and pharmacodynamics relationships for Salvianolic Acid B micro-porous osmotic pump pellets in angina pectoris rabbit - Shu-Ling Kan; Jin Li; Jian-Ping Liu; Hong-Liang He; Wen-Jing Zhang (Elsevier, 2014)
The work aims to investigate the in vitro release, pharmacokinetics (PK), pharmacodynamics (PD) and PK-PD relationships of Salvianolic Acid B micro-porous osmotic pump pellets (SalB-MPOPs) in angina pectoris New Zealand White (NZW) rabbits, compared with those of SalB immediate-release pellets (SalB-IRPs). The SalB plasma concentrations and Superoxide dismutase levels (PD index) were recorded continuously at predetermined time interval after administration, and the related parameters were calculated by using WinNonlin software. The release profile of MPOPs was more sustained than that of IRPs. PK results indicated that the mean Cmax was significantly lower, the SalB plasma concentrations were steadier, both area under concentration-time curve from 0 to 24 h (AUC0-24 h) and from 0 to infinity (AUC0-∞) were presented larger, and both the peak concentration time (Tmax) and mean residence time (MRT) were prolonged for MPOPs, as compared with those of IRPs. PD results suggested that peak drug effect (Emax) was lower and the equilibration rate constant (ke0) between the central compartment and the effect compartment was higher of MPOPs vs. those of IRPs. PK-PD relationships demonstrated that the effect-concentration-time (ECT) course of MPOPs was clockwise hysteresis loop, and that of IRPs was counter-clockwise hysteresis loop. Collectively, those results demonstrated that MPOPs were potential formulations in treating angina pectoris induced by atherosclerosis.